Eczema Herpeticum in Pregnancy - Grigoriy E. Gurvits; Jill A. Nord (PAGEPress Publications, 2011)
Eczema Herpeticum (EH), or Kaposi's varicelliform eruption, is a skin infection with herpes simplex type I virus (HSV-1) that occurs in patients with compromised skin integrity, such as atopic dermatitis (AD). Unrecognized, it may be fatal and viremia in pregnancy may lead to fetal demise and miscarriage. We describe a rare case of EH in pregnancy, eczema herpeticum gravidarum (EHG), which is the third published report in the literature to date.